Analytical Investigation to Improve the Buckling Capacity of Hollow Circular Pipe Columns - Faruqi, M; Gonzales, Lucas; Bailey, Breanna; Aguiniga, Francisco (European Journal of Applied Sciences, 2026)
Pipe columns subjected to high loads are prone to buckling and this is a cause of major concern for many industrial buildings, making it vital to find a solution to prevent buckling. Many industrial columns have been subjected to long-term stresses that leave the structure vulnerable to sudden loads or pressures. These sudden changes can cause deformations leaving the columns incapable of carrying their designed loads. This in turn leaves the whole structure at risk of failure. One solution is the pressurization of pipe column. The pressurization of pipes is a very cost-effective solution as there would be no extra materials needed. Thus, the aim of this was study was to analytically examine the effects of pressurization on hollow circular pipes. Analytical relationships between various parameters are presented. General results, show, that pressurization increases the buckling capacity of hollow circular pipe columns.